Identification of a Novel Papillomavirus Type (MfoiPV1) Associated with Acrochordon in a Stone Marten (Martes foina) - Urška Kuhar; Diana Žele Vengušt; Urška Jamnikar-Ciglenečki; Gorazd Vengušt (Pathogens, 2021)
Papillomaviruses (PVs) are an extremely large group of viruses that cause skin and mucosal infections in humans and various domestic and wild animals. Nevertheless, there is limited knowledge about PVs in wildlife hosts, including mustelid species. This study describes a case in stone marten (Martes foina) with a clinical manifestation of skin tumor, which is rather atypical for infections with PVs. The result of the papillomavirus PCR performed on the skin tumor sample was positive, and the complete PV genome was determined in the studied sample using next-generation sequencing technology. The analysis of the PV genome revealed infection of the stone marten with a putative new PV type belonging to the Dyonupapillomavirus genus. The proposed new stone marten PV type was named MfoiPV1.